The The Role of Glucosamine and Chondroitin Supplementation in the Management of Osteoarthritis. - M.Kaisar Febriantara; George Pestalozi; Helmi Ismunandar (CV. Jasa Sukses Abadi, 2026)
Osteoarthritis (OA) is a chronic degenerative disease characterized by progressive damage to articular cartilage and surrounding joint tissues, clinically manifesting as pain, deformity, and disability. The main risk factors include aging, joint injury or overuse, and obesity. According to the Global Burden of Disease Study in 2020, approximately 595 million people worldwide were living with osteoarthritis. In Indonesia, data from the 2018 Basic Health Research report indicated that osteoarthritis affected about 55 million individuals, with the highest prevalence among those aged over 61 years, accounting for 65%. Pathophysiologically, osteoarthritis develops due to cartilage thinning, leading to biomechanical changes, reduced synovial fluid, and increased inflammatory processes associated with aging. Inflammatory cells, particularly macrophages, release mediators that accelerate cartilage degradation and exacerbate joint pain. Radiological assessment of osteoarthritis severity is commonly performed using the Kellgren–Lawrence classification. Management of osteoarthritis frequently involves nonsteroidal anti inflammatory drugs, although long term use is associated with adverse effects. Therefore, adjunctive therapies such as glucosamine and chondroitin have been widely studied. Glucosamine and chondroitin exhibit anti inflammatory and chondroprotective effects and play roles in inhibiting cartilage degradation while supporting anabolic processes in cartilage tissue. Several studies have demonstrated that supplementation with glucosamine and chondroitin improves pain scores, slows joint space narrowing, and enhances joint function in patients with osteoarthritis. These findings suggest that glucosamine and chondroitin may serve as beneficial adjunctive therapies in the management of osteoarthritis.